Implementasi Sistem Tanggap Bencana dengan Metode Simple Triage and Rapid Treatment - Roby Stevi Lumbu (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
Disaster mitigation is a process that must be done so that the victim could be helped as soon as possible. This study aims to create a system of triage to provide information services quickly, efficiently, and effectively in disaster management. Methods This study focuses how to make triage information system, where victims disaster will grouped based on priorities through the triage process by using algorithms Siple Triage and Rapid Treatment (START) system thus built can be used by people who are not medical team. These results indicate that the system will provide the decision through the triage results to categorize by color. Victims are labeled red are critical and require the victim to the hospital treatment, the victim was a yellow label, green label handling of victims that can be postponed, while the black label indicates the patient is dead, the result would facilitate triage medical team in conducting further treatment. It can be concluded that the disaster triage information system can provide convenience in handling the victims based on the level of emergency.